Basic overview of method validation in the clinical virology laboratory. (30th August 2017) - Newman, Howard; Maritz, Jean
Summary: Diagnostic virology laboratories are an essential part of the health system and are often relied upon to provide information to clinicians that will inform clinical decision making. It is therefore imperative that diagnostic results produced in the laboratory are reliable. One way of ensuring quality results is by ensuring that all tests are either validated (for tests developed in‐house) or verified (for commercial assays that are FDA‐approved or CE‐labeled). In the diagnostic virology laboratory, these processes can be complex as both qualitative and quantitative measurements for serological and molecular tests are routinely offered. While there are numerous guidelines governing quality assurance in the virology laboratory, all accrediting agencies would insist on tests being validated or verified prior to implementation without providing explicit guidance to the process. As there is no universal guideline on the optimal way to perform validation/verification experiments, this review will provide a basic overview of method validation/verification, specific for clinical virology laboratories, and includes explanation of statistical analysis and acceptance/rejection criteria.